2015
DOI: 10.3329/uhj.v10i2.26123
|View full text |Cite
|
Sign up to set email alerts
|

Radial Artery Patency after Trans-radial Cardiac Catheterization in a Bangladeshi Population

Abstract: Background: Transradial cardiac catheterization (TCC) is now preferred method over trans-femoral approach globally including Bangladesh. But the incidence of radial artery occlusion (RAO) after TCC is not infrequent and it ranges from 1-18% in different studies. The aim of our study was to see the incidence of RAO after TCC in a population coming for coronary angiogram and/or coronary intervention and also to evaluate the factors responsible for RAO. Methods: The observational prospective study was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…Similarly, 63.8% with age >50 years were declared to be having RAO by Chowdhury. 12 Male into female percentage in our study was perceived to 63.4% versus 36.6% which is in line with the literature showed two thirds (66.7%) were male by Chowdhury. Another study reported comparable results with respect to gender (male 68.8% and female 32.2%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, 63.8% with age >50 years were declared to be having RAO by Chowdhury. 12 Male into female percentage in our study was perceived to 63.4% versus 36.6% which is in line with the literature showed two thirds (66.7%) were male by Chowdhury. Another study reported comparable results with respect to gender (male 68.8% and female 32.2%).…”
Section: Discussionsupporting
confidence: 91%
“…Incidence of hypertension, diabetes mellitus (DM), dyslipidemia and smoking were 80%, 65%, 57% and 38% respectively. 12 A Study by Tuncez had inverse results with respect to high percentage of female gender (56.6%) and Hypertension (81.1%) DM (34.9%) Hyperlipidemia (85%) Smoking (47.2%). 1 Mean interval of Cine-fluoroscopy for coronary angiography was 2.75 ± 1.5 min and percutaneous coronary intervention (PCI) 8.29 ± 5.1 minutes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5 of 6 French guides were used in our cases owing to the transradial access route. Besides this, due to smaller body build and relatively smaller diameter of the radial artery (2.2±0.03 mm) 20 in our population, we could not use guides larger than 6 French, due to potential radial artery spasm. In their study, Nemani, et al 14 reported that the guide hooked the coronary selectively in 40% patients, while it had to be kept off ostium co-axial with the coronary in 55% patients, deep intubation with monitoring of the pressure in 5% of cases, all of which were strikingly similar to our approach.…”
Section: Discussionmentioning
confidence: 95%